Thrombocytopenia in Dengue: Interrelationship between Virus and the Imbalance between Coagulation and Fibrinolysis and Inflammatory Mediators - Elzinandes Leal de Azeredo; Robson Q. Monteiro; Luzia Maria de-Oliveira Pinto (Hindawi Limited, 2015)
Dengue is an infectious disease caused by dengue virus (DENV). In general, dengue is a self-limiting acute febrile illness followed by a phase of critical defervescence, in which patients may improve or progress to a severe form. Severe illness is characterized by hemodynamic disturbances, increased vascular permeability, hypovolemia, hypotension, and shock. Thrombocytopenia and platelet dysfunction are common in both cases and are related to the clinical outcome. Different mechanisms have been hypothesized to explain DENV-associated thrombocytopenia, including the suppression of bone marrow and the peripheral destruction of platelets. Studies have shown DENV-infected hematopoietic progenitors or bone marrow stromal cells. Moreover, anti-platelet antibodies would be involved in peripheral platelet destruction as platelets interact with endothelial cells, immune cells, and/or DENV. It is not yet clear whether platelets play a role in the viral spread. Here, we focus on the mechanisms of thrombocytopenia and platelet dysfunction in DENV infection. Because platelets participate in the inflammatory and immune response by promoting cytokine, chemokine, and inflammatory mediator secretion, their relevance as "immune-like effector cells" will be discussed. Finally, an implication for platelets in plasma leakage will be also regarded, as thrombocytopenia is associated with clinical outcome and higher mortality.